THE FAILURE OF COSMOPOLITANISM: THE LAICITE RULES AS A CRISIS OF FRENCH MUSLIMS - Sholihin, Fitri (State Islamic University of Datokarama Palu, 2021)
This paper discusses the increasingly visible failure of cosmopolitanism in France. Laïcité rules are considered as a form of cosmopolitanism that determines between religion and the State, but currently, laïcité are considered as a